Enhancing Customer Loyalty in Mushroom Seed Market: Role of Product Quality and After-Sales Service: Meningkatkan Loyalitas Pelanggan di Pasar Bibit Jamur: Peran Kualitas Produk dan Layanan Purna Jual - Sholikha, Tasya Fahillatus; Purwanto, Nuri (Indonesian Journal of Law and Economics Review, 2023)
This study addresses the escalating competition in the mushroom seed market, particularly in East Java, where producers strive to bolster customer loyalty through product quality and after-sales service enhancements. Employing an explanatory research approach, 100 respondents were purposively sampled to assess the impact of product quality and after-sales service on customer loyalty for Nilam Jamur Jombang. Data was collected using questionnaires and analyzed through SPSS software. Results highlight a significant positive influence of both product quality and after-sales service on customer loyalty, emphasizing the potential for heightened loyalty with improved product quality and enhanced post-purchase support. This research contributes valuable insights for businesses seeking to thrive in a competitive market environment. Highlight: Intensifying Market Competition: This study delves into the mushroom seed market's intensifying competition, particularly in East Java, where producers strategically enhance customer loyalty through improvements in product quality and after-sales service. Research Approach and Sample: Employing an explanatory research approach, the study involves 100 purposively sampled respondents, focusing on the impact of product quality and after-sales service on customer loyalty in Nilam Jamur Jombang. Enhanced Loyalty Factors: Analysis using SPSS software unveils a significant positive correlation between product quality, after-sales service, and customer loyalty. The findings underscore the potential for heightened loyalty, emphasizing the significance of improved product quality and effective post-purchase support strategies in a competitive market landscape. Keyword: Mushroom Seed Market, Customer Loyalty, Product Quality, After-Sales Service, Competitive Environment